Women forest defenders and inclusive institutionalism: Assessing gender capacity and policy instruments in community-based forestry - Lutfia Azizah (Jurnal Bisnis Kehutanan dan Lingkungan, 2026)
Background: The Social Forestry (SF) Scheme is a national policy that aims to enhance community livelihoods while ensuring ecological sustainability. It does so by providing local communities with access to forest management. In West Nusa Tenggara (NTB) Province, the area under various management models encompasses 60,160 hectares, exhibiting considerable promise for the advancement of agroforestry, non-timber forest products (NTFPs), and ecotourism. However, the program continues to encounter substantial implementation challenges, particularly with regard to the involvement of women. Despite the substantial contributions of women to NTFP processing, household economics, and the maintenance of traditional ecological knowledge, their involvement in formal decision-making remains limited due to socio-cultural norms, gender-insensitive policies, the absence of gender-disaggregated data, and a male-dominated licensing system. Method: The present study analyzes the implementation of Social Forestry in NTB. This analysis is based on a systematic review of secondary documents, including national and regional policy documents, PIAPS, official social forestry statistics, civil society organization reports, and peer-reviewed scientific articles. The study focuses on assessing policy relevance. Policy relevance is defined as the alignment between the objectives, instruments, and mechanisms of Social Forestry policies with the principles of inclusive governance and gender equality in implementation practices. The present study employs a descriptive qualitative approach and thematic analysis of the document corpus. Finding: Social Forestry in NTB has evolved through the following mechanisms: the strengthening of forest-based economies, the consolidation of community institutions, and the adoption of adaptive agroforestry practices. These outcomes are strengthened by the program's integration into the Integrated Regional Development (IRD) framework. However, the extent of women's participation remains constrained and often symbolic, with persistent disparities in leadership, planning, and resource control despite their high involvement in production activities. Conclusion: It is evident that initiatives such as the Women Forest Defenders (WFD) program signify advancements in enhancing gender capacity. However, a comprehensive and empirically substantiated evaluation of the efficacy of policy instruments remains deficient. Therefore, the enhancement of gender capacity, the refinement of policy instruments, the provision of gender-disaggregated data, and the integration of women's roles throughout the Social Forestry value chain are imperative prerequisites for achieving equitable, inclusive, and sustainable Social Forestry governance. Novelty/Originality of this article: The study's primary contribution lies in its systematic mapping of the Social Forestry policy framework and instruments in NTB from a gender governance perspective, thereby identifying discrepancies between policy design and implementation practices at the ground level.